Pemanfaatan Internet dalam Meningkatkan Kinerja Penyuluh Pertanian di Kabupaten Cianjur - Purwatiningsih, Nanik Anggoro; Fatchiya, Anna; Mulyandari, Retno Sri Hartati (Jurnal Penyuluhan, 2018)
As the science and technology have developed rapidly, as well as current globalization, farmer’s needs are increasingly diverse nowadays. Therefore, extension workers are required to develop their abilities according to current conditions and challenges. But in reality the competencies of extension workers was still low. The low competence of extension workers resulted in low performance as well. It was influenced by the lack of training that has been held for extension workers. Based on this point, it is necessary to improve the performance of extension workers, utilizing the internet media can be an answer which is very rapidly growing at this time. This study analyzed: 1) the level of internet media utilization, 2) factors influencing internet utilization, and 3) the effect of internet utilization on extension worker performance. Field research conducted in January-March 2017 in Cianjur Regency. The sample of research were 26 government extension workers and 74 contract-based extension workers. Descriptive statistics and inferential statistics (Multiple Linear Regression) was used for analytical method. The results showed that the use of internet by extension workers was moderate, especially for the preparation of reports, the design of extension methods, preparation of “programma” and design extension method. The result of the analysis showed that factors influencing internet usage were age, formal education, internet perception, duration, and diversity of accessed internet media. Performance of extension-workers to increase internet utilization effectively is needed for increase information and insight to be applied to farmers. As the science and technology have developed rapidly, as well as current globalization, farmer’s needs are increasingly diverse nowadays. Therefore, extension workers are required to develop their abilities according to current conditions and challenges. But in reality the competencies of extension workers was still low. The low competence of extension workers resulted in low performance as well. It was influenced by the lack of training that has been held for extension workers. Based on this point, it is necessary to improve the performance of extension workers, utilizing the internet media can be an answer which is very rapidly growing at this time. This study analyzed: 1) the level of internet media utilization, 2) factors influencing internet utilization, and 3) the effect of internet utilization on extension worker performance. Field research conducted in January-March 2017 in Cianjur Regency. The sample of research were 26 government extension workers and 74 contract-based extension workers. Descriptive statistics and inferential statistics (Multiple Linear Regression) was used for analytical method. The results showed that the use of internet by extension workers was moderate, especially for the preparation of reports, the design of extension methods, preparation of “programma” and design extension method. The result of the analysis showed that factors influencing internet usage were age, formal education, internet perception, duration, and diversity of accessed internet media. Performance of extension-workers to increase internet utilization effectively is needed for increase information and insight to be applied to farmers.